Healing steps a journey celebrating music, dance & friendship - Leland, Marc; Gemini Films (Australia : Contemporary Arts Media, 1996)
Profiling four artists who had to cope with adversity, while persevering in their respective performing arts careers, this documentary celebrates the healing and retrospective powers of music, dance and friendship
Title from title screen
Photographed by Ben Wolf ; editor, Michael Bulkley
Narrated by Carmet Kirtland
DVD format
Keywords: Dance -- Physiological aspects; Dance -- Health aspects; Music; Exercise